2014
DOI: 10.3109/09593985.2014.994250
|View full text |Cite
|
Sign up to set email alerts
|

A clinical reasoning model focused on clients’ behaviour change with reference to physiotherapists: its multiphase development and validation

Abstract: This unique model, theory- and evidence-informed, has been developed to help physiotherapists to apply clinical reasoning systematically in the process of behaviour change with their clients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 88 publications
2
47
0
2
Order By: Relevance
“…It has also been shown that a focus on pain, rather than on progress, can result in increased time to return to prior level of function [7]. Additionally, Elven et al reported that a patient with a greater perception of self-worth is more likely to recover from an injury [47]. Conversely, fear and anxiety related to pain from the injury, work, or other external influences can contribute to the deleterious factors preventing healing and returning to prior level of function [7] [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that a focus on pain, rather than on progress, can result in increased time to return to prior level of function [7]. Additionally, Elven et al reported that a patient with a greater perception of self-worth is more likely to recover from an injury [47]. Conversely, fear and anxiety related to pain from the injury, work, or other external influences can contribute to the deleterious factors preventing healing and returning to prior level of function [7] [46].…”
Section: Discussionmentioning
confidence: 99%
“…Fear as the result of pain has been shown to decrease function and increase avoidance of activities that may provoke pain [7] [48]. Accurately determining a patient's FABs can be critical in knowing how to appropriately provide external motivation [47] [48].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the proposed strategy to clinical reasoning for exercise therapy in complex cases is not exclusive. Other approaches, for example the clinical reasoning model by Elven et al integrating behavioral change into physiotherapy, can be complementary [24]. Behavior change strategies are an integral part of the application of exercise therapy.…”
Section: Case Knee Osteoarthritis 64 Years Old Womanmentioning
confidence: 99%
“…Behavior change strategies are an integral part of the application of exercise therapy. Specific goal setting and reviewing of goals, shaping knowledge, and promoting feedback and reinforcement are some examples of strategies for behavior change [24]. Patients' ability to change their exercise behavior and adhere to an exercise regimen is highly dependent on psychological and social factors.…”
Section: Case Knee Osteoarthritis 64 Years Old Womanmentioning
confidence: 99%
“…In addition, the evidence for applying cognitive and behavioural methods in client management (Brunner et al, 2013;Linton and Shaw, 2011;Williams, Eccleston, and Morley, 2012;Åsenlöf, Denison, and Lindberg, 2009) supports the incorporation of these methods also in the clinical reasoning process. Thus, the client's behaviours and goals as well as the use of behaviour change strategies are features of a theory-and evidence-based clinical reasoning process (Elvén, Hochwälder, Dean, and Söderlund, 2015). To support investigations of physiotherapists' clinical reasoning abilities, in accordance with theory-and evidence-based methods that promote health behaviour change, a new instrument should reflect the characteristics of such an approach.…”
Section: Introductionmentioning
confidence: 99%